Analysis of HFE gene mutations and HLA-A alleles in Brazilian patients with iron overload - Cançado, Rodolfo Delfini (2006)
CONTEXT AND OBJECTIVE: Hemochromatosis is a common inherited disorder of iron metabo- lism and one of the most important causes of iron overload. The objective was to analyze the presence of C282Y, H63D and S65C muta- tions in the HFE gene and HLA-A alleles for a group of Brazilian patients with iron overload, and to correlate genotype with clinical and laboratory variables. DESIGN AND SETTING: Prospective study, in Discipline of Hematology and Oncology, Facul- dade de Ciências Médicas da Santa Casa de Misericórdia de São Paulo. METHODS: We studied 35 patients with iron overload seen at our outpatient unit between January 2001 and December 2003. Fasting levels of serum iron and ferritin, and total iron- binding capacity, were assayed using standard techniques. Determinations of C282Y, H63D and S65C mutations in the HFE gene and of HLA-A alleles were performed by polymerase chain reaction (PCR). RESULTS: Twenty-six out of 35 patients (74%) presented at least one of the HFE gene muta- tions analyzed. Among these, five (14%) were C282Y/C282Y, four (11%) C282Y/H63D, one (3%) H63D/H63D, six (17%) C282Y/WT and ten (29%) H63D/WT. No patients had the S65C mutation and nine (25%) did not present any of the three HFE mutations. Four out of five patients with C282Y/C282Y genotype (80%) and three out of four patients with C282Y/H63D genotype (75%) were HLA A*03. CONCLUSION: Analysis of HFE gene mutations constitutes an important procedure in identifying patients with hereditary hemochromatosis, par- ticularly for patients with iron overload.